USULAN DESAIN KEMASAN MINYAK GORENG DENGAN MENGGUNAKAN METODE SELEKSI KONSEP STUDI KASUS PT. PULAU SAMBU KUALA ENOK KEC. TANAH MERAH KAB. INHIL - Erwin Prawijaya; Roberta Zulfhi Surya (Program Studi Teknik Industri, 2017)
In this study, research conducted at PT. Pulau Sambu Kuala Enok PT. Pulau Sambu Kuala Enok is a company that engaged in processing coconut oil that located in Tanah Merah Village Tanah Merah Subdistrict Indragiri Hilir Regency Riau Province. PT. Pulau Sambu Kuala Enok has been popular with processing coconut oil to cooking oil. In this study he writer are discusses the Proposed of Packaging Desing of Cooking Oil using Selection Concept Method Study Case in PT. Pulau Sambu Kuala Enok Kec. Tanah Merah Kab. Inhil. This design does not refer to the design of the company’s brand. So far, the progblem is done in direct bulk to ship tnak for export purpose, the problem in retailment (packaging product) has not been developed and give input related to discourse to produce cooking oil at PT. Pulau Sambu Kuala Enok in packaging section is the factors that must be implemented by the company to improve the quality of packaging design of PT. Pulau Sambu Kuala Enok and related variables in the packaging design of PT. Pulau Sambu Kuala Enok.